2018
DOI: 10.1007/s10753-018-0820-9
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-37 Attenuates Bleomycin-Induced Pulmonary Inflammation and Fibrosis in Mice

Abstract: Pulmonary fibrosis is a disease with chronic inflammation and excessive collagen deposition for which there is no effective treatments. Interleukin (IL)-37 is a newly identified anti-inflammatory cytokine but its role in pulmonary fibrosis remains unclear. In this study, we investigated the effect of IL-37 on bleomycin-induced pulmonary fibrosis in mice. A lentivirus expressing IL-37 was administered intranasally to bleomycin-induced C57BL/6 mice. We found that IL-37 improved the survival of mice and reduced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 41 publications
0
6
0
1
Order By: Relevance
“…More and more data suggested that inflammation involved in the pathogenesis of CAP, promoted the occurrence and development of CAP (27,28). Several inflammatory cytokines were increased and inflammatory signaling pathways were activated in the progress of CAP (17,29). The levels of proinflammatory cytokines were compared between two groups in our research.…”
Section: The Association Between Serum Il-37 and The Prognosis In Cap Patientsmentioning
confidence: 82%
See 1 more Smart Citation
“…More and more data suggested that inflammation involved in the pathogenesis of CAP, promoted the occurrence and development of CAP (27,28). Several inflammatory cytokines were increased and inflammatory signaling pathways were activated in the progress of CAP (17,29). The levels of proinflammatory cytokines were compared between two groups in our research.…”
Section: The Association Between Serum Il-37 and The Prognosis In Cap Patientsmentioning
confidence: 82%
“…In addition, an experimental study in vivo found that IL-37 transgenic mice evoked excessive inflammation and tissue damage in murine pneumococcal pneumonia (16). Moreover, mounting evidences revealed that IL-37 plays a crucial protective role in non-small cell lung cancer, murine allergic asthma, fibrosis, and airway inflammation by alleviating inflammation (17)(18)(19). These results indicated that IL-37 may involve in the pathophysiological process of several pulmonary diseases.…”
Section: Introductionmentioning
confidence: 95%
“…Accordingly, we measured lower TGF-β mRNA levels in livers of IL-37tg mice after CCl 4treatment. Li et al also showed that intranasal administration of a lentivirus expressing IL-37 improved survival, attenuated pulmonary inflammation and collagen deposition in bleomycintreated mice (52). In summary, these reports lead us to speculate that, beside limiting the inflammatory response, IL-37 directly impacts HSC-mediated liver fibrogenesis by interacting with TGF-β dependent pathways.…”
Section: Figure 7 |mentioning
confidence: 95%
“…Treatment with the anti-inflammatory cytokine IL-37 attenuated BLM-induced PF by inhibiting collagen deposition and inflammatory infiltration into the lungs. IL-37 treatment reduced MCP-1, IL-6, and TNF-α expression and induced IFN-γ expression in lung tissue [ 89 ].…”
Section: Soluble Immune Modulators In Pulmonary Fibrosismentioning
confidence: 99%